Universal growth modes of high-elevation conifers - Datsenko, N. M.; Sonechkin, D. M.; Büntgen, U. (Ulf); Yang, B. (Dendrochronologia, 2016)
In order to characterize the main growth modes of high-elevation conifers, such as typical variations inherent to annual tree growth records, we resolved eigen problems related to intra-record correlation coefficient matrices of several large sample sets for (A) very long-lived Chinese junipers and (B) shorter-lived European pines and larches. Such modes allow for the identification of tree growth variations of different origins, i.e., resulting from climate and/or microenvironments as well as origins that are purely biological in nature. We determined that these modes are universal, namely, that they are identical for both ring width (RW) and maximum latewood density (MXD) records. Certain specific shapes found in these main modes were indicative of anomalous tree growth. Cross-correlations between identical modes related to RW and MXD data were determined to be nonessential. This suggests that RW and MXD data likely represent different aspects of tree growth response to varying climatic and environmental conditions. (C) 2016 Elsevier GmbH. All rights reserved.